Optimization of a Single Expander LNG Process. (2015) - Austbø, Bjørn; Gundersen, Truls
Abstract: A single expander process with nitrogen as refrigerant has been optimized for liquefaction of natural gas. Comparisons have been made between a simplified process model assuming constant specific heat capacities and ideal gas behavior for the refrigerant, and a rigorous model employing the Soave-Redlich-Kwong equation of state. For the simplified model, equations have been developed that enable an analytical solution to the optimization problem. Quite surprisingly, there is good agreement between the models when the minimum temperature difference is small. For the remaining cases, better solutions are obtained from the rigorous model accounting for the non-ideal behavior of the refrigerant.